Blueprint: heart bracelet / Nur Nafisha Omar Razi...[et al.] - Omar Razi, Nur Nafisha; Ahmad, Nurul Hidayah; Hasnan, Nur ' Ainul Nasrin; Sanusi, Hawa (2017)
HEART BRACELET was first established on 10th September 2017. HEART BRACELET is not the only company in Malaysia that produce smartwatch or smart bracelet. But we wish to acquire national within three years. We see it as our main mission to provide high quality, higher standard lower prices and better service to the targeted markets. Basic corporate objective is reflected in everything that we do, which is contribute to the enrichment of the quality of lives for people around the world. Our product mainly targeted for people that suffer from heart problems but it also suitable for all ages as it is multifunction. Every family from the lower to high income family can afford to buy our products as the price we offer is very reasonable compared to the other brands. HEART BRACELET are especially appealing to person that suffer from heart disease. According to National Heart Institute, IJN (February 23,2017), they received 300,000 patients, while on 2016, they received 280,000 patients that having treatment in the IJN. The director of IJN mentioned that the total number of patient that suffer from heart problem is increasing 5% to 7% each year. The minimum price that will be spend for our product will only RM250, therefore we can predict about each 33% of customer in Malaysia will attract with our product. This 33% is the total number of the person that suffer from heart problems. As our product more focus to this problem. The total market size for our product is about RM 23,085,000.00. This product also has potential profitability because it is a new invention product by us. People nowadays are more prone to use the latest products in order to follow the latest technology trend. Other than this product will might save one of your family member's life. So, I believe that one will not doubt to buy this product for themselves or their family members hence our product is very cheap compared to the other brands. Our management aim to providing excellence in our product and services, continuous effort to expand new market , enhancement of research and development on a long range perspective commitment to care for end users through providing even better service after sale and pursuit of further globalization. Other than that, by having the competitor around us, it helping us to keep thinking and researching new enhancement that can be done in order to give the customer a very good quality of product yet with a suitable prices.